2017
DOI: 10.2174/1389557517666170228115324
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen and Nitrogen Species in Carcinogenesis: Implications of Oxidative Stress on the Progression and Development of Several Cancer Types

Abstract: There is now common agreement that reactive oxygen and nitrogen species are involved in the development and progression of several human cancers like breast, prostate, colorectal, gynecological, cervical, eye, skin, leukemia, gastric. Antioxidant supplements at low doses can promote health, while excess supplementation can be harmful and even carcinogenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 0 publications
1
81
0
2
Order By: Relevance
“…Intracellular ROS may induce DNA damage and chromosome instability and activate apoptotic pathways to induce cancer cell death. 20 Several studies have reported that Que has an antioxidative effect that can quench ROS, reactive nitrogen species, and other radicals. 21,22 Li et al showed that low concentration of Que decreased the cytotoxic effect of cisplatin by reducing intracellular ROS in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS may induce DNA damage and chromosome instability and activate apoptotic pathways to induce cancer cell death. 20 Several studies have reported that Que has an antioxidative effect that can quench ROS, reactive nitrogen species, and other radicals. 21,22 Li et al showed that low concentration of Que decreased the cytotoxic effect of cisplatin by reducing intracellular ROS in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been considered as a major contributor to the development of skin cancers, such as melanoma [144][145][146]. Accordingly, antioxidants, including resveratrol, have been used to prevent and treat skin cancer [147][148][149], although exacerbation and increased risk of cancers have been reported [150,151]. Melanoma is the most serious type of skin cancer, with mortality rates of 3.1/100,000 in the US [152] and 1.4-1.9/100,000 in Germany [153].…”
Section: Anticancermentioning
confidence: 99%
“…In addition to ROS, other reactive species have notable impacts on redox biology and, consequently, on oxidative stress. These include the reactive nitrogen species (RNS) [starting with the reaction of nitric oxide Brought to you by | University of California -Irvine Authenticated Download Date | 5/4/19 12:43 AM (˙NO) with O 2˙− to form peroxynitrite (ONOO − ), Figure 1] (Kruk and Aboul-Enein, 2017), reactive sulfur species (RSS) (i.e. persulfides, polysulfides and thiosulfate, which can oxidize and inhibit thiol-proteins and enzymes) (Nishida et al, 2016), reactive carbonyl species (RCS) (i.e.…”
Section: Oxidative Stress and The Intracellular Redox State In Melanomentioning
confidence: 99%